The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12889-020-08934-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual and community level factors associated with anemia among lactating mothers in Ethiopia using data from Ethiopian demographic and health survey, 2016; a multilevel analysis

Abstract: Background: Maternal anemia is a worldwide public health problem especially in developing countries including Ethiopia. The anemia burden among lactating mothers was higher in Africa particularly in Ethiopia, and scant attention was paid. To date, there is limited evidence on community level determinants of anemia among lactating mothers in Ethiopia. This study, therefore, aimed to assess the prevalence and factors associated with anemia among lactating mothers in Ethiopia. Methods: Secondary data analysis was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
103
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(121 citation statements)
references
References 29 publications
13
103
5
Order By: Relevance
“…Our study also revealed that modern contraceptive use was associated with anemia in women of reproductive age. Using modern contraceptive methods reduces the prevalence of anemia and this is in concordance with different studies [20,32,48]. This is because women who used modern contraceptive methods prevent complications related to pregnancy and childbirth, which could eventually reduce the prevalence of anemia due to recurrent blood loss.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study also revealed that modern contraceptive use was associated with anemia in women of reproductive age. Using modern contraceptive methods reduces the prevalence of anemia and this is in concordance with different studies [20,32,48]. This is because women who used modern contraceptive methods prevent complications related to pregnancy and childbirth, which could eventually reduce the prevalence of anemia due to recurrent blood loss.…”
Section: Discussionsupporting
confidence: 83%
“…According to different studies done worldwide; age [ 27 , 28 ], educational level [ 29 31 ], occupation [ 32 , 33 ], marital status [ 20 , 34 , 35 ], wealth status [ 20 , 21 , 29 , 30 , 36 ], sex of household head [ 32 , 37 , 38 ], media exposure [ 39 – 41 ], body mass index [ 20 , 29 , 35 , 42 ], type of toilet facility and source of drinking water [ 21 , 29 ], ever had of terminated pregnancy [ 39 , 43 , 44 ], parity [ 36 , 45 ], household size [ 46 , 47 ], modern contraceptive use [ 20 , 48 ], current pregnancy status [ 21 , 28 , 30 , 35 , 45 ], currently breastfeeding [ 30 , 39 ], residence [ 49 ], and community literacy level [ 32 ] are associated with anemia in women of reproductive age.…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that a unit change in maternal parity had a significant positive effect on the Hb concentration of mothers in the two lower quantiles (5th and 10th) in Mozambique. These findings are inconsistent with some previous studies which suggest that higher parity is associated with increased odds of anaemia in women of reproductive age 25,[47][48][49] . For example, a study in Ethiopia observed that lactating mothers who had three or more births were at higher risk of anaemia relative mothers who had one birth 47 .…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are inconsistent with some previous studies which suggest that higher parity is associated with increased odds of anaemia in women of reproductive age 25,[47][48][49] . For example, a study in Ethiopia observed that lactating mothers who had three or more births were at higher risk of anaemia relative mothers who had one birth 47 . However, it is significant to point out that the present study did not treat parity as a categorical variable.…”
Section: Discussioncontrasting
confidence: 99%
“…Globally, 54.1% of anemia cases contribute to mild, 42.5% moderate, and 3.4% severe problems in all age groups of the population of the world ( 8 , 9 ). The magnitude of anemia among lactating mothers is 52.5% in South Asia ( 4 ), 60.3% in Myanmar, 20% in Nepal, 63% in India, and 28.3% in Ethiopia ( 4 , 6 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%